Aplicación de juegos para el desarrollo de la motricidad fina de niñas y niños del primer grado de educación general básica de la escuela Alejandro Campoverde Andrade del cantón Pasaje. Periodo lectivo 2014-2015 - Ruilova Regalado, Tatiana Elizabeth (2015)
Speaking of nursery education, we refer to the development of the capacities of children being the object of study personal and social, training immersed in the educational process applied by teachers.